Implementation of a Web-Based Booking and Monitoring Information System at Tirta Jawi Resort Using Laravel and Midtrans Payment Gateway Integration - Della Fitriastuti; Annisa Zalzabilla Rahmawati; Muhammad Fahrudin Wahyu Nugroho; Zulaikha Hesty Rahmawati (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Information technology transformation has reshaped operational landscapes across industrial sectors, particularly tourism. Tirta Jawi Resort, operating as a local tourism destination, experiences operational bottlenecks in managing ticket and facility reservations through manual processes. The research develops a web-based information system to streamline reservation procedures, facility monitoring, and digital payment integration via the Midtrans platform. The system employs Laravel framework with prototyping methodology, enabling gradual user requirement validation. Primary functionalities include swimming pool ticket reservations, villa and pavilion bookings, restaurant menu orders, real-time transaction reporting, and Midtrans payment gateway integration. System evaluation utilizes PIECES analysis to measure operational performance improvements, process efficiency, and service quality enhancement. Implementation results demonstrate substantial improvements in transaction processing speed, operational monitoring ease, and manual recording error reduction. The system generates added value through round-the-clock service accessibility, automated reporting transparency, and digital market expansion, enabling the resort to strengthen competitive positioning within tourism digitalization trends.